PENGARUH MEDIA FLASHCARD BERBASIS KEARIFAN LOKAL JEPARA DALAM PENINGKATAN KARAKTER SOSIAL BUDAYA SISWA KELAS 4 SD N 3 BANYUMANIS - Ninis Fivtia Sari; F. Shoufika Hilyana; Nur Fajrie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
PENGARUH MEDIA FLASHCARD BERBASIS KEARIFAN LOKAL JEPARA DALAM PENINGKATAN KARAKTER SOSIAL BUDAYA SISWA KELAS 4 SD N 3 BANYUMANIS Ninis Fivtia Sari1, F. Shoufika Hilyana2, Nur Fajrie3 PGSD FKIP Universitas Muria Kudus 1202033273@std.umk.ac.id, 2farah.hilyana@umk.ac.id, 3nur.fajrie@umk.ac.id 087834130582 ABSTRACT Socio-cultural character is a character value that students must possess because socio-cultural character is very important in social and state life. However, there are many students in Indonesia who still have low levels of social and cultural character. Therefore, the research aims to determine the influence of the socio-cultural character of grade 4 students at SD N 3 Banyumanis before and after using flashcards based on Jepara local wisdom and how big the influence is. This research is quantitative research. The experimental research design used was Pre-experimental One Group Pretest-Posttest Design. This research was conducted on grade 4 students at SD N 3 Banyumanis with a total of 22 students. The data in this research was collected using a questionnaire. Data will be analyzed using the T-Test. The results of this research can be seen from the average scores where in the pretest the average score was 226.13, while in the posttest the average score was 235.36. Then the T-test obtained a significance value of 0.000 < 0.05. So it can be concluded that the conclusion Ha is accepted and H0 is rejected, which means that there is an influence of using flashcards based on local Jepara wisdom to improve socio-cultural character in class 4 of SD N 3 Banyumanis.